Trophic State Waters of Kolong Tin Post Mining Based on Phytoplankton in Baran Timur Village Karimun Regency, Kepulauan Riau Province - Bukit, Friska Lesmana Beru; Dahril, Tengku; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract There were many activites in kolong of tin post mining in Baran Timur Village, Karimun Regency, Kepulauan Riau Province, contributed organic and inorganic materials that influenced concentration of nutrient (N and P) in the water and affect phytoplankton abundance and finally trophic state of waters. This research aims to know the trophic state waters of kolong tin post mining in Baran Timur Village Karimun Regency Kepulauan Riau Province based on phytoplankton abundance. A research was conducted during July 2019. There were three stations namely Station 1 (inlet area), Station 2 (in middle of kolong) and Station 3 (outlet area). There were 3 vertical sampling points, in the surface, in 2 Secchi depth and in 4 Secchi depth. Sampling was done 3 times, once/week. Result shown the abundance of phytoplankton was 23,918–179,758 sel/L, concentration of nitrate 0.043-0.061 mg/L, phosphate 0.085-0.135 mg/L, pH 5, dissolved oxygen 4.10-6.91 mg/L, free carbondioxide 3.32-7.32 mg/L, temperature 30.3-310C, transparency 73.3-78 cm and depth4-7 m. Based on phytoplankton abundance, the trophic state waters of kolong tin post mining in Baran Timur Village Karimun Regency Kepulauan Riau Province was mesotrophic. Keyword: Trophic State, Phytoplankton, Kolong Tin Post Mining